Conventional and Inverse Magnetocaloric Effect in Ni-Rich Ni-Mn-Ga and Ni-Mn-Sn Heusler Alloy: A Comparison - Pal, D. (Journal of Scientific Research, 2020)
Magnetic and magnetocaloric effect of Ni-rich Ni52Mn34Sn14 (Ni-Mn-Sn) and Ni54Mn17Ga29 (Ni-Mn-Ga) Heusler alloys have been investigated up to a magnetic field of 5T and within a temperature range of 4.2 – 325 K. In this study, we report a systematic comparison between Ni-rich Ni52Mn34Sn14 and Ni54Mn17Ga29 alloys in the light of their magnetocaloric effect (MCE). In both the samples, a large magnetic entropy change was observed (~96 J kg-1 K-1 for Ni-Mn-Ga), but for the alloy Ni-Mn-Sn the MCE becomes negative/inverse. From various magnetic measurements it have been observed that in Ni-Mn-Sn alloy the martensite to austenite transition accompanied by lower to higher magnetization whereas for Ni-Mn-Ga alloy reverse situation occurred. The different type of magnetocaloric effect, i.e. inverse and direct can be explained by considering magneto-crystalline anisotropy and different state of magnetization of the martensite and austenite phase of the alloys.